Peripheral nerve responses to hand-arm vibration - Sakurai, Tadayoshi; Matoba, Tsunetaka (Scandinavian Journal of Work, Environment & Health, 1986)
Electromyograms from the arm, shoulder,and neck wererecordedwithsurface electrodes, and the transmission of vibration to the hand, arm, shoulder, and forehead was measured. Nerve conduction velocity in the median nerve of the forearm and palm was assessed in vibrating tool operators. Low-frequencycomponents of less than 20 Hz in electromyograms of the arm and shoulder were significantlyintensified with increasing levels of vibration amplitude and gripping strength during the experiment.The amplitude of the transmitted vibration particularly influencedthe electromyographic results. The maximal motor and sensory nerve conduction velocities of vibrating tool operators were significantly lower than those of a healthy reference group.
Keywords: arm; electromyogram; hand; hand-arm vibration; low-frequency component; nerve conduction velocity; nerve response; peripheral nerve response; vibration; vibration transmission